Shifting Perspectives in Pensions - Marek Góra; Edward Palmer (Institute for the Study of Labor (IZA), 2004)
This paper addresses the questions of what is an economically efficient pension system, what are the externalities and what are the risks of the four alternative pension systems: financial defined contribution (FDC), notional or non-financial defined contribution (NDC), financial defined benefit (FDB) and non-financial defined benefit (NDB). A main contribution of the paper is the development of the concept of NDC, itself a new construction in pension economics. An important conclusion is that NDC is neutral in terms of externalities. It manages the risks and eliminates the negative externalities associated with traditional public NDB schemes, and in a manner similar to FDC schemes.
Keywords: D91; H55; J26; H23; D8; G23; D6; 330; pensions; NDC; FDC; notional account systems; financial account systems; funding; externalities; risks; defined contribution; government debt; Gesetzliche Rentenversicherung; Umlageverfahren; Kapitaldeckungsverfahren; Wirtschaftliche Effizienz; Externer Effekt